Antibody-Based Methods Reveal the Protein Expression Properties of Glucosinolate Sulfatase 1 and 2 in Plutella xylostella. Issue 6 (30th November 2022) - Xiong, Yu; Jiang, Chaoyang; Amir, Muhammad Bilal; Dong, Yuhong; Xie, Lianjie; Liao, Yuan; He, Weiyi; Lu, Zhanjun; Chen, Wei
Abstract: The glucosinolates (GLs) and myrosinase defensive systems in cruciferous plants were circumvented by Plutella xylostella using glucosinolate sulfatases (PxGSSs) during pest-plant interaction. Despite identifying three duplicated GSS-encoding genes in P. xylostella, limited information regarding their spatiotemporal and induced expression is available. Here, we investigated the tissue- and stage-specific expression and induction in response to GLs of PxGSS1 and PxGSS2 (PxGSS1/2) at the protein level, which shares a high degree of similarity in protein sequences. Western blotting (WB) analysis showed that PxGSS1/2 exhibited a higher protein level in mature larvae, their guts, and gut content. A significantly high protein and transcript levels of PxGSS1/2 were also detected in the salivary glands using WB and qRT-PCR. The immunofluorescence (IF) and immunohistochemistry (IHC) results confirmed that PxGSS1/2 is widely expressed in the larval body. The IHC was more appropriate than IF when autofluorescence interference was present in collected samples. Furthermore, the content of PxGSS1/2 did not change significantly under treatments of GL mixture from Arabidopsis thaliana ecotype Col-0, or commercial ally (sinigrin), 4-(methylsulfinyl)butyl, 3-(methylsulfinyl)propyl, and indol-3-ylmethyl GLs indicating that the major GLs from leaves of A. thaliana Col-0 failed to induce the expression of proteins for both PxGSS1 and PxGSS2. Our study systemically characterized the expression properties of PxGSS1/2 at the protein level, which improves our understanding of PxGSS1/2-center adaptation in P. xylostella during long-term insect-plant interaction.